Detecting non-germinomatous germ cell tumor component by arterial spin labeling perfusion-weighted MR imaging in central nervous system germ cell tumor. Issue 136 (March 2021) - Takano, Motoki; Kinoshita, Yasuyuki; Sugiyama, Kazuhiko; Kolakshyapati, Manish; Takayasu, Takeshi; Yonezawa, Ushio; Taguchi, Akira; Akiyama, Yuji; Amatya, Vishwa Jeet; Takeshima, Yukio; Kurisu, Kaoru; Yamasaki, Fumiyuki
Abstract: Purpose: Differentiating between germinoma and non-germinomatous germ cell tumor (NGGCT) is important because sensitivity to chemotherapy and/or radiotherapy is quite different between these two subgroups. In this study, we evaluated whether the arterial spin labeling (ASL) based perfusion-weighted imaging (PWI) could provide additional information for the differential diagnosis between germinoma and NGGCT. Method: Between 2011 and 2018, 20 patients with central nervous system (CNS) germ cell tumor (GCT) who underwent preoperative MR imaging including ASL-PWI were enrolled in this study. Relative tumor blood flow (rTBF) was evaluated on ASL-PWI by manually placing regions of interest at gadolinium enhanced part of the tumors and normal subcortical white matter. Presence of intratumoral T1 hyperintense foci and apparent diffusion coefficient (ADC) were also evaluated. The final diagnosis was made by the combination of tumor markers and the histological diagnosis. Results: Among 20 patients of CNS-GCT, 11 were diagnosed as germinoma and 9 were diagnosed as NGGCT. In the germinoma subgroup, the rTBF ranged from 0.90 to 1.71 (mean 1.21, median 1.09), while it ranged from 1.14 to 5.75 (mean 3.91, median 3.31) in NGGCT subgroup. The receiver operating characteristic (ROC) curve showed that calculating rTBF is useful for differentiating between germinoma and NGGCT (area under the curve (AUC) 0.929, P = 0.0012) compared to intratumoral T1 hyperintense foci (AUC 0.788, P = 0.0304) and ADC (AUC 0.919, P = 0.0016). Conclusions: High rTBF obtained by ASL-PWI implied the presence of NGGCT component. This information might help in deciding the chemotherapy/radiotherapy intensity.